2014
DOI: 10.1021/es5004044
|View full text |Cite
|
Sign up to set email alerts
|

New Strategy To Enhance Phosphate Removal from Water by Hydrous Manganese Oxide

Abstract: Hydrous manganese oxide (HMO) is generally negatively charged at circumneutral pH and cannot effectively remove anionic pollutants such as phosphate. Here we proposed a new strategy to enhance HMO-mediated phosphate removal by immobilizing nano-HMO within a polystyrene anion exchanger (NS). The resultant nanocomposite HMO@NS exhibited substantially enhanced phosphate removal in the presence of sulfate, chloride, and nitrate at greater levels. This is mainly attributed to the pHpzc shift from 6.2 for the bulky … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(70 citation statements)
references
References 42 publications
5
65
0
Order By: Relevance
“…Further research has been done in recent years to search for adsorbent materials suitable for industrial production with high adsorption efficiency [6][7][8][9][10][11][12]. Studies have shown that phosphorus in eutrophic water exists as free phosphate, and a large amount of metal oxide/hydroxide has been used in phosphorus removal because of its specific affinity for phosphate including hydrous ferric oxide [13], magnetite [14], hydrous manganese oxide [15], aluminum hydroxide gel [16], lanthanum hydroxide [17], cerium oxide [18], titanium dioxide [19], hydrous niobium oxide [20], and zirconium oxide/hydroxide [21,22], etc. However, the adsorption capacity of these adsorbents is not high enough (usually <100 mg•g −1 ) and most of them are unsuitable for commercial production due to the complexity of the production process.…”
Section: Introductionmentioning
confidence: 99%
“…Further research has been done in recent years to search for adsorbent materials suitable for industrial production with high adsorption efficiency [6][7][8][9][10][11][12]. Studies have shown that phosphorus in eutrophic water exists as free phosphate, and a large amount of metal oxide/hydroxide has been used in phosphorus removal because of its specific affinity for phosphate including hydrous ferric oxide [13], magnetite [14], hydrous manganese oxide [15], aluminum hydroxide gel [16], lanthanum hydroxide [17], cerium oxide [18], titanium dioxide [19], hydrous niobium oxide [20], and zirconium oxide/hydroxide [21,22], etc. However, the adsorption capacity of these adsorbents is not high enough (usually <100 mg•g −1 ) and most of them are unsuitable for commercial production due to the complexity of the production process.…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, adsorption is being increasingly used in research on phosphorus removal because of its high efficiency and relatively simple application. Thus, diverse adsorbents have been used for phosphorus removal, such as Kanuma mud, Mg 3 -Fe layered double hydroxides, hydrous manganese oxide, and grapheme-nanosheet-supported lanthanum hydroxide nanoparticles [4,[9][10][11]. Nickel hydroxide and nickel oxide materials have received much attention in recent years for application in alkaline secondary batteries, fuel cells, electrochemical capacitors, electrolyzers, electrosynthetic cells, and electrochromic devices [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The Fe(III) can also affect the removal and recovery of phosphate in anaerobic sludge digestion [37,288] . Adsorption of phosphate onto MnO2 has also been reported previously [227,228] . In addition, the anaerobic biodegradation with Fe(III) is also efficient in nitrogen (ammonia) removal [232,372] .…”
Section: Sustainabilitysupporting
confidence: 59%
“…Complete DFC removal is obtained when the concentration is 116 mg P⋅L -1 . PO4 3can adsorb onto the MnO2 surface, which decreases the reactive surface sites for DFC removal [228] . On the other hand, PO4 3can decrease the inhibition effects of Mn 2+ generated from DFC removal by forming Mn3(PO4)2 [127] .…”
Section: Effect Of Phosphatementioning
confidence: 99%